Peranan Kualitas Layanan Terhadap Keputusan Pembelian Pengguna e-Commerce pada Siswa Sekolah - Yansela; Mahendra, A; Lisa (Journal of Trends Economics and Accounting Research, 2023)
Service quality is a dynamic state that is closely related to products, services, human resources, as well as processes and the environment that can at least meet or even exceed the expected service quality. Purchasing decisions are an integration process used to combine knowledge to evaluate two or more alternative behaviors and choose one of them. The problem examined in this research is the role of service quality in the purchasing decisions of e-commerce users at the Tunas Baru school. The purpose of this research is to determine the role of service quality and product quality on purchasing decisions. The research method used is an associative quantitative method via an online questionnaire. The total sample was 51 Tunas Baru High School students from a population of 108 students taken using nonprobability sampling techniques with an incidental sampling approach. The research results show that service quality plays a role in purchasing decisions by 30.5%. The solution that researchers can provide is to further improve human resources (HR) in providing services to prospective buyers who want to buy or just ask questions. Because getting good quality service will make potential customers feel satisfied. Consumers will feel satisfied if they get good service or as expected. By providing good service, apart from being able to play a role in purchasing interest and making purchasing decisions, it can also make buyers turn into customers which will help us promote our shop.